Chemoproteomic analysis of the promising candidate molecule of the indole derivative with lab code SV-1010 and other non-steroidal anti-inflammatory drugs - Pavel A. Galenko-Yaroshevsky; Ivan Yu. Torshin; Andrey N. Gromov; Ivan A. Reyer; Olga A. Gromova; Tereza R. Glechyan; Konstantin F. Suzdalev; Andrey V. Zadorozhniy; Anait V. Zelenskaya (Research Results in Pharmacology)
Introduction: For effective and safe pharmacotherapy of pain, it is important to evaluate the mechanisms and spectrum of action of non-steroidal anti-inflammatory drugs (NSAIDs), including their effect on the proteom, central effect, as well as pain relieving and anti-inflammatory effects. The aim of the study was to evaluate the complex of differences between the promising candidate-molecule of indole derivative SV-1010 and the well-known NSAIDs.